Blasting Vibration Monitoring and a New Vibration Reduction Measure - Xi Yang; Yunpeng Zhang; Jie Wang (Journal of Engineering and Technological Sciences, 2022)
Vibration waves generated by blasting can cause shock to buildings. Different responses occur in different parts of the building. Therefore, a single standard is inaccurate. At the same time, methods to reduce vibration are needed. In this paper, the variation of peak particle velocity (PPV) and principal frequency was analyzed. The energy variation of blast vibration waves was analyzed by wavelet packet decomposition. A numerical model was established to verify the new vibration reduction measure. The results showed that the PPV on the walls increases with their height. The PPV and principal frequency of different structures of single-story brick-concrete buildings are different. The amplification factor of PPV does not change much when the principal frequency ratio is larger than 0.75. Measuring points at different heights have different sensitivities to blasting vibration waves of different principal frequencies. Therefore, different structures will respond differently to the same blasting operation. The PPV can be reduced by waveform interference. However, the cycle of blasting vibration waves decreases with increasing distance. Therefore, it is necessary to determine a reasonable interval to reduce the PPV. This requires further research.